2014
DOI: 10.1089/ars.2013.5420
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 Deacetylates ATP Synthase F1 Complex Proteins in Response to Nutrient- and Exercise-Induced Stress

Abstract: Our data suggest that acetylome signaling contributes to mitochondrial energy homeostasis by SIRT3-mediated deacetylation of ATP synthase proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
132
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(139 citation statements)
references
References 29 publications
5
132
2
Order By: Relevance
“…In contrast, the increase in parasite proliferation, movement, and differentiation observed for TcSir2rp3-ox cell lines might be explained in part by changes in the activity of key enzymes of the metabolic control and oxidative stress response, known to be regulated by acetylation in the mitochondria of different organisms (50)(51)(52). For example, acetylation controls the activity of superoxide dismutase (53,54), ATP synthase (F 1 F 0 ATPase) (55), and acetyl-CoA synthetase (56,57). The fact that overexpression of a mutated version of TcSir2rp3 without enzymatic activity does not affect growth and differentiation supports the notion that deacetylation of mitochondrial targets is responsible for the observed phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the increase in parasite proliferation, movement, and differentiation observed for TcSir2rp3-ox cell lines might be explained in part by changes in the activity of key enzymes of the metabolic control and oxidative stress response, known to be regulated by acetylation in the mitochondria of different organisms (50)(51)(52). For example, acetylation controls the activity of superoxide dismutase (53,54), ATP synthase (F 1 F 0 ATPase) (55), and acetyl-CoA synthetase (56,57). The fact that overexpression of a mutated version of TcSir2rp3 without enzymatic activity does not affect growth and differentiation supports the notion that deacetylation of mitochondrial targets is responsible for the observed phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The proteins of the ATP synthase complex undergo numerous posttranslational modifications that can be altered by energy status or oxidative stress; these modifications can affect both the formation and activity of the complex (63)(64)(65)(66). One recent example is the inhibition of ATP synthase by acetylation in the absence of the mitochondrial deacetylase sirtuin 3, which is activated by NAD + (64), showing that alterations in redox status can influence ATP synthase activity. Despite the low ATP synthase activity in Acsl1 T2/2 hearts, activated AMPK is lower than in controls and ATP content is normal (9), indicating sufficient ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the first publication identifying an SIRT3 downstream deacetylation target was acetylcoenzyme A synthetase (ACS), providing the first seminal data that SIRT3 plays a critical role in energy homeostasis. Since then, other SIRT3 targets that direct energy metabolism have been characterized, which include long-chain acyl-coenzyme A dehydrogenase (LCAD), 3-hydroxy-3-methylglutaryl coenzyme A synthase 2 (HMGCS2), and all proteins that comprise the adenosine triphosphate (ATP) synthase complex (28,38,43,81,89).…”
Section: Sirtuins and Human Breast Cancermentioning
confidence: 99%
“…In this regard, it has been shown that SIRT3 directs the function of tricarboxylic acid cycle activity by deacetylating pyruvate dehydrogenase (61), isocitrate dehydrogenase (IDH) (75), ACS (37,72), and glutamate dehydrogenase (GDH) (70). It has also been shown that SIRT3 directs ATP production via the deacetylation of electron transport chain subunits (complexes I-III and ATP synthase) (25,81). SIRT3 also participates in fatty acid metabolism by deacetylating LCAD and HMGCS2 (1, 37, 39).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation